Phytoremediation potential of urban tree (pongamia pinnata) in removing heavy metals from contaminated soils affected by Mn-based industrial waste - Nurul Nabila, Mohd Azman (Universiti Malaysia Sarawak (UNIMAS), 2015)
In this study, the phytoremediation potential of pongamia pinnata in remediating soils contaminated by Mn-based industrial waste were assessed and determined. A pot experimental study was conducted in evaluating the potential of P. pinnata in translocating selected heavy metals (mainly Mn) from the soils contaminated with industrial waste. Seeds of P. pinnata were germinated and later transplanted to plastic pots at different treatments: control (T0), topsoil + 10% Mn slag (T1), topsoil + 30% Mn slag (T2), and topsoil + 50% Mn slag (T3).